Resistive sensor array readout circuit : Nodal array approach - Muhammad Farid Akmal, Fahrurrazi; Airul Sharizli, Abdullah; Fairuz Rizal, Mohamad Rashidi (Institution of Engineering and Technology, 2022)
In this paper, Nodal Array Approach (NAA) will be chosen in implementing readout circuit for pressurize touch sensor in hand grip application sensor array. We proposed a comparison methods of readout topology for resistive sensor array in terms of the circuit complexity, measurement error, and sensor capacity.